Implementasi PDS di Perguruan Tinggi 2019 - Nurmalasari, Dewi (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
Learning is the process of delivering knowledge that can influence and play an important role in determining a person's learning success. In this case, learning has a close relationship with learning methods and strategies. In order for the learning process to run effectively, a learning strategy is needed. So a teacher must plan and design learning strategies by applying learning models with the aim of facilitating students in the learning process. In addition, the confidence of a student is very important to support the learning process. On the one hand, there are still many students who have fewer communication levels, with the use of EYD which is also lacking. Judging from the experience, the application of discovery learning is applied. Discovery learning is one of the learning models that is oriented towards students wherein the learning process the teaching staff is a facilitator who directs students to find a concept or principle regarding the existing problems. Thus, students are encouraged to play an active role in the learning process. Therefore students must be trained to be skilled and independent and think critically about existing problems, this can be obtained through the Student Central Learning learning model. In addition to practicing students must also evaluate themselves on what things should get more attention so they can maximize their potential.